The end of tutelage of orphans in the Early Modern urban society (Theatrum historiae, 2010)
According to municipal law of the Early Modern Period a tutelage of an orphanu- sually ended in two ways: when the orphan reached the full-age or died before. Less fre- quent reason for ending a tutelage was depriving the tutor of his duties because of faults in the administration of orphans ́ heritage. In the case that a widow-woman happens to be the tutor of the children, we speak about tutela anomala. This kind of tutelage was usually ended after her new marriage. In that case usually, at least in practice, either an adult son of the family or widow's new husband became the tutor. The duty of every tutor, with the exception of the so called powerful-father tutor, was to render accounts to the orphan at the end of the tutelage and, in the case of his fault, to pay deficiency. After that the orphan becomes a full-fledged owner of the iherited property. In practice, however, the process of getting the money back to the full-aged child, whether it had been placed on deposit at the townhall or at the tutors', usually protracted for many years. Thelaw was also concerned with money lent at interest during the period of tutelage. The full-aged orphan could not take his/her property all at once, but in installments, into which the loan was divided. The tutor did not profit unless the child, or all the children, have died, in that case the tutor was entitled to the third part of the orphan's heritage. According to the law tutor is not entitled to any remuneration, the performance of this duty was therefore probably primarily a matter of personal honor and self-presentation.